Corrosion Behavior of Passivated 316LSS with Ag Coating as PEMFC Bipolar Plate. (9th October 2011) - Huang, Naibao; Liang, Chenghao; Wang, Hongtao; Xu, Lishuang; Xu, Hongfeng
Abstract : A new chemical passivation technique, which contained 20 g/L hydrogen peroxide, 3.75 g/L sodium silicate, 1.25 g/L sodium carbonate, 3.75 g/L lactic acid and 0.75 g/L 8-hydroxyquinoline, was used to modify 316 stainless steel with Ag coating (Ag-coated 316SS) as PEMFC bipolar plates. The results indicated that the compact passive film had been obtained on the surface of Ag-coated 316SS. The passivation process could not only increase contact angle (from58 ∘ to104 ∘ ) but also decreased pinhole defects of Ag-coated 316SS. Electrochemical test manifested that the passivation process could reduce Ag-coated 316SS's double layer capacitance (C d ), and increase its charge transfer resistance. So, it provided significant protection against corrosion for Ag-coated 316SS in PEMFC environment.